Assessment of Polydopamine to Reduce Streptococcus mutans Adhesion to a Dental Polymer (2023)
: Bacterial adhesion to the surface of materials is the first step in biofilm formation, which will lead to conditions that may compromise the health status of patients. Recently, polydopamine (PDA) has been proposed as an antibacterial material. Therefore, the objective of the current work was to assess and compare the adhesion of Streptococcus mutans to the surface of poly(methyl methacrylate) (PMMA) discs that were modified using PDA following a biomimetic approach versus smooth PDA-coated PMMA surfaces. In addition, an assessment of the growth inhibition by PDA was performed. PMMA discs were manufactured and polished; soft lithography, using the topography from the Crocosmia aurea leaf, was used to modify their surface. PDA was used to smooth-coat PMMA discs by dip-coating. The growth inhibition was measured using an inhibition halo. The surfaces were characterized by means of atomic force microscopy (AFM), the contact angle (CA), and Fourier-transform infrared spectroscopy (FTIR). Polydopamine exhibited a significant antibacterial effect when used directly on the S. mutans planktonic cells, but such an effect was not as strong when modifying the PMMA surfaces. These results open the possibility of using polydopamine to reduce the adhesion and growth of S. mutans, which might have important consequences in the dental field.